(untitled) (Research, Society and Development, 2020)
Wireless sensor networks have been widely used in recent years, both in industry and in homes, to automate environments. The study aims to develop a Wireless Sensor Network using the ZigBee protocol to monitor light, temperature and presence, with the addition of a load trigger lamp, in the monitored environment. As a result, the devices used to implement the network and the validation through tests performed were presented.